2010
DOI: 10.1091/mbc.e10-01-0062
|View full text |Cite
|
Sign up to set email alerts
|

MiR-322/424 and -503 Are Induced during Muscle Differentiation and Promote Cell Cycle Quiescence and Differentiation by Down-Regulation of Cdc25A

Abstract: This article describes a novel role of Cdc25A down-regulation during differentiation of proliferating myoblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(166 citation statements)
references
References 50 publications
10
153
0
3
Order By: Relevance
“…4E). In line with these results, the expression levels of cyclin D1 (Ccnd1), cyclin E (Ccne1), and Cdc25a cell cycle genes (45,46) resulted in downregulation (Fig. 4F).…”
Section: Figsupporting
confidence: 77%
“…4E). In line with these results, the expression levels of cyclin D1 (Ccnd1), cyclin E (Ccne1), and Cdc25a cell cycle genes (45,46) resulted in downregulation (Fig. 4F).…”
Section: Figsupporting
confidence: 77%
“…We also note that Cdc25 and Ccnd messenger RNAs that are targets of miR-195/497 likely also play a role in cell cycle withdrawal before terminal myogenic differentiation. The downregulation of Cdc25 in differentiating C2C12 myoblasts in the presence of miR-322/424 and miR-503 promotes cell cycle arrest necessary for terminal differentiation, while the downregulation of Ccnd2 in neonatal myoblasts enhances muscle cell fusion 32,33 . It remains to be seen whether miR-195/497 are also involved in cell cycle arrest during the terminal differentiation of myoblasts, and whether MuSCs require similar miRNA regulation of Cdc25/Ccnd mRNAs to form skeletal muscle fibres.…”
Section: Resultsmentioning
confidence: 99%
“…They are thought to play negative regulatory roles posttranscriptionally, causing mRNA cleavage or translation repression, by targeting the imperfect complementary sequences, usually located in the 3 0 -untranslated regions (UTRs) of mRNAs [1]. It has been reported that miRNAs are involved in various biological processes, including the cell cycle, differentiation and tumorigenesis [2][3][4]. Additionally, the temporal and spatial specificity that is frequently associated with development and differentiation is another characteristic of miRNA expression [5,6].…”
Section: Introductionmentioning
confidence: 99%